Fluorine-containing methyl acrylate polymer, self-cleaning coating, preparation method and application thereof
By preparing fluorine-containing methacrylate polymers and forming a crosslinking network, the problem of high adhesion between high viscosity liquid and solid surface is solved, and self-cleaning of high viscosity liquids, durability and substrate adaptation are achieved for the self-cleaning of high viscosity liquids and coating durability and substrate adaptation are achieved. , ensuring the stability and consistency of the coating on different substrates.
Patent Information
- Application Number
- CN202110631544.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2020-06-09
- Filing Date
- 2021-06-07
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2041-06-07
AI Technical Summary
In the prior art, the adhesion between high viscosity liquid and solid surface is high, and the self-cleaning performance of ultra-synoptic solid surfaces to high viscosity liquids is difficult to achieve. Most methods rely on reactive substrates, which limit their in different types. Universal application on substrate materials.
By preparing fluorine-containing methacrylate polymers, using them to form a crosslinking network during solution polymerization, and combining specific monomer compositions and crosslinking agents to prepare a coating with excellent self-cleaning properties. This coating ensures its adaptability and durability on different substrates by regulating the monomer composition and crosslink density.
Effective self-cleaning of high viscosity liquids is achieved, the durability and substrate adaptability of the coating are improved, and the stability and performance consistency of the coating on different substrates is ensured.
Smart Images

Figure CN113773437B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a fluorine-containing methyl acrylate polymer, a self-cleaning coating, and a preparation method and application thereof. Background Art
[0002] Self-cleaning is the property of a material that can keep its surface clean by removing impurities and bacteria attached to its surface spontaneously with the help of water, sunlight, gravity and other natural conditions based on its own surface properties. This self-cleaning phenomenon originated from people's observation of nature. The lotus leaf that "emerges from the mud without being stained" is the most typical self-cleaning surface. In addition, the leaves of many plants and the wings of insects in nature have self-cleaning properties, and most of them have special wettability.
[0003] Currently, there are three main types of self-cleaning surfaces: (1) self-cleaning surfaces with superhydrophilic properties; (2) self-cleaning surfaces with superhydrophobic or superoleophobic properties; and (3) self-cleaning surfaces with superlubricant properties.
[0004] (1) A surface with super-hydrophilic properties can make water droplets form a uniformly spread water film between the dirt and the surface. Under the action of gravity and other external forces, the dirt can automatically fall off with the flow of the water film, thus achieving a self-cleaning effect. The most effective material for preparing super-hydrophilic coatings is TiO 2 However, based on TiO 2 The self-cleaning performance of the surface must be achieved under ultraviolet light, which limits its wide application.
[0005] (2) Water droplets or oil droplets can form liquid beads that can roll down freely on a surface with superhydrophobic or superoleophobic properties. The liquid beads can roll down freely under the action of gravity and other factors to avoid contamination of the surface and achieve a self-cleaning effect. The principle of preparing superhydrophobic or superoleophobic surfaces is to prepare them by using a rough micro-nano composite structure with hydrophobic or oleophobic surface chemical modification. The contact angle of the droplet on this type of chemical surface is greater than 150°, and the rolling angle is less than 10°. Although this type of surface has excellent self-cleaning properties, it has extremely stringent requirements on the morphology of its micro-nano composite structure. Related studies have shown that only micro-nano composite structures with a "reentrant convex" morphology can meet the requirements for preparing this type of surface. The preparation of this structure usually involves complex technologies, such as ion etching, reverse nanoimprinting, photolithography, etc., and the coating prepared by this method is usually opaque. It is not suitable for large-scale and low-cost preparation, and at the same time limits its universal application on different types of substrate materials, and cannot meet the needs of practical applications.
[0006] (3) On a self-cleaning surface with super-slip properties, the droplet can slide down at a lower sliding angle regardless of the static contact angle of the droplet. There are two specific methods:
[0007] The first method is inspired by the structure of the tropical carnivorous plant Nepenthes, and a liquid surface is prepared by injecting a perfluorinated liquid (lubricant) into a porous micro-nanostructured substrate. When water or oil droplets come into contact with this liquid surface, a liquid-liquid interface with super-slippery properties is formed, on which the droplets can easily slide down at a low sliding angle. However, this type of surface needs to be prepared on a substrate material with a porous micro-nanostructure, which limits the universality of this method on different substrate materials. Moreover, in practical applications, the main problem with super-slippery liquid self-cleaning surfaces or organic gel materials based on liquid lubricant infusion is that the volatility and fluidity of the lubricant itself will cause it to be continuously consumed during use (especially in high temperature environments, the lubricant is easy to volatilize), causing the corresponding surface or gel material to lose its self-cleaning properties.
[0008] The second method is to graft a monolayer of low surface energy liquid (such as low molecular weight polydimethylsiloxane (PDMS), perfluoroalkyl or perfluoropolyether) onto the substrate. The monolayer of polymer grafted on the surface of the substrate gives the surface a "liquid-like" property, which is conducive to the sliding of the liquid. However, this coating is composed of a monolayer of polymer and is damaged by wear during use, has a very limited lifespan, and lacks durability.
[0009] In order to solve the durability problem of the monolayer super-slippery water / lubricating oil self-cleaning coating, people have grafted low molecular weight polydimethylsiloxane (PDMS), perfluoroalkyl or perfluoropolyether into the polymer cross-linked network using polyurethane and other reactions to prepare super-slippery water / lubricating oil self-cleaning coatings. For example, Liu et al. synthesized highly cross-linked polyurethane using perfluoropolyether or PDMS, then dissolved the polyurethane in organic solvents such as tetrahydrofuran, and finally cast the polyurethane solution on the substrate and cured it at 120°C to prepare a transparent super-slippery liquid self-cleaning coating. This method effectively solves the above-mentioned problems of evaporation or leakage of the lubricating liquid, poor optical transparency and durability. However, because the adhesion between high-viscosity liquid and solid surface is very large, the self-cleaning performance of solid surface based on slippery liquid properties for high-viscosity liquid is difficult to achieve. So far, few super-slippery liquid solid self-cleaning surfaces that can achieve self-cleaning of high-viscosity liquids have been reported.
[0010] Moreover, the coating prepared by this method generally requires a high cross-linking density of the polymer, because when the cross-linking is insufficient, the coating surface will be reconstructed, resulting in a decrease in the self-cleaning property of the surface. At the same time, when such coatings are applied to substrates, organic solvents such as tetrahydrofuran are generally required, which will corrode or dissolve some substrates (for example, plastics).
[0011] It can be seen that although some methods for preparing super-slippery liquid self-cleaning surfaces have been developed, there are still some problems that need to be solved. For example, because the adhesion between high-viscosity liquids and solid surfaces is very large, the self-cleaning performance of super-slippery liquid solid surfaces for high-viscosity liquids is difficult to achieve, and these problems need to be solved urgently. Most of the methods reported so far for preparing super-slippery liquid self-cleaning surfaces rely on reactive substrates, which limits their universal application on different types of substrate materials. Summary of the invention
[0012] The technical problem to be solved by the present invention is to overcome the defects in the prior art that the adhesion between high-viscosity liquid and solid surface is very large, and the self-cleaning performance of super-lubricant solid surface for high-viscosity liquid is difficult to achieve, and provide a fluorine-containing methyl acrylate polymer, a self-cleaning coating and a preparation method and application thereof.
[0013] The present invention solves the above technical problems through the following technical solutions.
[0014] The present invention provides a method for preparing a fluorine-containing methacrylate polymer, wherein the raw materials of the fluorine-containing methacrylate polymer include a polymerization monomer, an initiator and a solvent;
[0015] The polymerizable monomer is monomer A, or monomer A and monomer B; monomer A is 2-(perfluorooctyl)ethyl methacrylate (PFDA); monomer B includes one or more of methyl acrylate (MA), methyl methacrylate (MMA), styrene (PS), methoxyethyl acrylate and n-butyl methacrylate (BMA);
[0016] After initiation by the initiator, the polymerizable monomer is subjected to solution polymerization to obtain the fluorine-containing methyl acrylate polymer; wherein the mass ratio of the polymerizable monomer to “the polymerizable monomer and the solvent” is 1 to 50%;
[0017] When the polymerizable monomers are the monomer A and the monomer B, the molar ratio of the monomer A to the monomer B is at least 0.5:1.
[0018] In the present invention, the monomer A or the monomer B can be obtained commercially.
[0019] In order to make the Young's modulus of the coating prepared from the fluorinated methacrylate polymer comparable to that of the substrate, those skilled in the art can select the type of the monomer B according to actual needs. For example, when a coating with a higher Young's modulus needs to be prepared, the monomer B can be a monomer containing a rigid group; when a coating with a lower Young's modulus needs to be prepared, the monomer B can be a monomer containing a flexible chain.
[0020] In the present invention, the amount of the initiator used can be conventional in the art, preferably 0.1-10% of the mass of the polymerized monomer, more preferably 0.5-1.5%, for example 1%, of the mass of the polymerized monomer.
[0021] In the present invention, the initiator may be a free radical initiator conventionally used in the art for free radical polymerization, such as azobisisobutyronitrile (AIBN) and / or dimethyl azobisisobutyrate (AIBME). The initiator is generally commercially available.
[0022] Preferably, the initiator is purified. The purification operation and conditions can be conventional in the art, and generally, purification is performed by recrystallization. Preferably, purification can be performed by the following method: after filtering the solution containing the initiator for the first time, the obtained filtrate is cooled and crystallized, and after filtering for the second time, the filter cake is collected and dried.
[0023] The temperature of the solution containing the initiator can be generally conventional, such as 60-80° C. The solvent in the solution can be any solvent conventional in the art that can dissolve the initiator, such as an alcohol solvent. The alcohol solvent is preferably anhydrous ethanol. The solution containing the initiator is generally obtained by heating and stirring.
[0024] The operation and conditions of the first filtration may be conventional in the art, and generally the solution containing the initiator is filtered while hot.
[0025] The operation and conditions of the cooling crystallization can be conventional in the art, and generally, cooling crystallization can be performed at room temperature. The cooling crystallization time can be 0.5 to 2 hours, for example, 1 hour.
[0026] The drying operation and conditions may be conventional in the art, for example, drying may be performed at room temperature and then vacuum drying.
[0027] In the present invention, the solvent may be a conventional organic solvent in the art that can dissolve the polymerizable monomer, such as N,N-dimethylformamide.
[0028] In the present invention, preferably, the raw material further comprises a cross-linking agent. The cross-linking agent can be a cross-linking agent conventionally used in the art for cross-linking reactions of such monomers, preferably N,N-methylenebisacrylamide (MBAA).
[0029] In order to make the Young's modulus of the coating prepared from the fluorinated methacrylate polymer equal to that of the substrate, those skilled in the art may choose whether to add a crosslinking agent or the amount of the crosslinking agent to be added according to actual needs. For example, when a coating with a higher Young's modulus needs to be prepared, a crosslinking agent may be added or the amount of the crosslinking agent may be appropriately increased; when a coating with a lower Young's modulus needs to be prepared, no crosslinking agent may be added.
[0030] The amount of the crosslinking agent used may be 0-5% of the molar amount of the polymerizable monomer, preferably 0-1%.
[0031] In the present invention, when the polymerizable monomer is only the monomer A, preferably, the raw material further comprises a cross-linking agent. The type and amount of the cross-linking agent are as described above.
[0032] In the present invention, when the polymerizable monomers are the monomer A and the monomer B, the molar ratio of the monomer A to the monomer B is at least 0.5: 1. If the content of monomer A is too low, the obtained product is in a gel state, and the gel state product does not have a self-cleaning effect.
[0033] Preferably, the molar ratio of the monomer A to the monomer B is 1:1 or more, more preferably 1.5:1 or more, for example 2:1, 4:1, 5:1, 8:1 or 10:1.
[0034] In the present invention, the monomer B is preferably the methyl acrylate, the methyl methacrylate, the styrene, the methoxyethyl acrylate or the n-butyl methacrylate, and more preferably the methyl acrylate or the n-butyl methacrylate.
[0035] In the present invention, the polymerizable monomer is preferably the 2-(perfluorooctyl)ethyl methacrylate and the methyl acrylate.
[0036] When the polymerizable monomers are the 2-(perfluorooctyl)ethyl methacrylate and the methyl acrylate, the molar ratio of the 2-(perfluorooctyl)ethyl methacrylate to the methyl acrylate is preferably (0.5-10):1, more preferably (1-8):1, for example 2:1, 4:1 or 5:1.
[0037] When the polymerizable monomers are the 2-(perfluorooctyl)ethyl methacrylate and the methyl acrylate, preferably, the raw material further comprises a crosslinking agent, and the type and amount of the crosslinking agent are as described above.
[0038] In the present invention, the polymerizable monomer is preferably the 2-(perfluorooctyl)ethyl methacrylate and the n-butyl methacrylate.
[0039] When the polymerizable monomers are the 2-(perfluorooctyl)ethyl methacrylate and the n-butyl methacrylate, the molar ratio of the 2-(perfluorooctyl)ethyl methacrylate to the n-butyl methacrylate is preferably (0.5-10):1, more preferably (1-8):1, for example 2:1, 4:1 or 5:1.
[0040] In the present invention, the operation and conditions of the solution polymerization may be conventional in the art. Generally, in the presence of the solvent and the initiator, the polymerization monomers may be subjected to solution polymerization.
[0041] Preferably, the initiator is added into a mixed solution containing the polymerization monomers to carry out the solution polymerization.
[0042] The mixed solution can be prepared by conventional methods in the art, for example, the solvent and the polymerizable monomer can be mixed uniformly by heating and stirring. There are no special requirements for the temperature and time of the heating and stirring, as long as the polymerizable monomer can be completely dissolved in the solvent. The temperature of the heating and stirring is preferably 60 to 70° C., for example, 65° C. The time of the heating and stirring is preferably 0.2 to 1 h, for example, 0.5 h.
[0043] When the raw material of the fluorine-containing methacrylate polymer includes a crosslinking agent, the crosslinking agent is generally in the mixed solution.
[0044] In the present invention, the temperature of the solution polymerization is preferably 60-70°C, more preferably 62-68°C, for example 65°C.
[0045] In the present invention, the solution polymerization time is preferably 20 to 30 hours, such as 24 hours.
[0046] In the present invention, the mass ratio of the polymerizable monomer and "the polymerizable monomer and the solvent" needs to be in the range of 1 to 50%. If the mass ratio is lower than 1%, the obtained product has a low molecular weight and is liquid at room temperature, and a coating cannot be prepared; if the mass ratio is higher than 50%, a polymer with an appropriate molecular weight and a self-cleaning effect cannot be obtained.
[0047] Preferably, the mass ratio of the polymerizable monomer to "the polymerizable monomer and the solvent" is 5 to 45%, more preferably 10 to 30%, and most preferably 16.7 to 20%.
[0048] In the present invention, preferably, the reaction solution after the solution polymerization is post-treated. The post-treatment operation can be conventional, generally cooling, washing, filtering, and drying the obtained filter cake.
[0049] The cooling is generally natural cooling to room temperature. The washing is for removing unreacted polymerized monomers, and is generally washed with ether for multiple times. The drying operation and conditions may be conventional in the art.
[0050] The present invention also provides a fluorine-containing methacrylate polymer prepared by the preparation method of the fluorine-containing methacrylate polymer.
[0051] In the present invention, the melting point of the fluorine-containing methacrylate polymer may be 60-120°C, for example, 72.1°C, 84.7°C, 85.9°C or 88.7°C.
[0052] In the present invention, the decomposition temperature of the fluorine-containing methacrylate polymer may be above 250°C, such as 256°C, 272°C, 276°C or 278°C.
[0053] The present invention also provides a self-cleaning coating, the raw material of which is the fluorine-containing methacrylate polymer as mentioned above.
[0054] In the present invention, the thickness of the self-cleaning coating can be adjusted according to actual needs, and is generally 0.005 to 0.1 mm, such as 0.02 to 0.06 mm.
[0055] In the present invention, the self-cleaning coating can be prepared by conventional methods in the art, for example, by solvent-free hot scraping.
[0056] The present invention also provides a method for preparing the self-cleaning coating, which comprises the following steps: scraping the melted fluorine-containing methacrylate polymer on a substrate to a desired thickness.
[0057] In the present invention, the substrate can be a rigid substrate or a flexible substrate selected according to actual needs. The rigid substrate generally refers to a conventional substrate material that is rigid, fixed, and cannot be bent, such as glass or stainless steel. The flexible substrate generally refers to a conventional substrate material that is variable or bendable, such as polyethylene terephthalate (PET), polyimide substrate (PI) or polytetrafluoroethylene substrate (Teflon). Before use, the substrate is generally subjected to conventional drying treatment.
[0058] When the polymerizable monomer of the fluorine-containing methacrylate polymer is only the monomer A, or is "the monomer A and the methyl acrylate", preferably, the substrate is a rigid substrate.
[0059] When the polymerizable monomers of the fluorine-containing methacrylate polymer are "the monomer A and the n-butyl methacrylate", preferably, the substrate is a flexible substrate.
[0060] In the present invention, the substrate may be placed on a heating table and heated to 10° C. or higher than the melting point of the fluorinated methacrylate polymer, such as 11.3° C., 14.1° C., 15.3° C., or 27.9° C., to melt the fluorinated methacrylate polymer.
[0061] In the present invention, in order to obtain a coating with uniform thickness, before the scraping, a tape of the required thickness is generally attached to the edge of the substrate, the fluorinated methacrylate polymer is placed on the edge of the substrate, and after melting, a scraping rod is used to closely adhere to the substrate and slowly push along the edge at a uniform speed to form a coating on the substrate with the same thickness as the tape.
[0062] The present invention also provides a self-cleaning composite coating, which comprises a photothermal layer and the above-mentioned self-cleaning coating, wherein the photothermal layer comprises a substance having a photothermal conversion effect.
[0063] In the present invention, the substance having a light-to-heat conversion effect is preferably selected from one or more of the following substances: metal nanoparticles, carbon-based light-absorbing materials, polymer light-absorbing materials, and two-dimensional transition metal carbides or carbonitrides (Mxene).
[0064] The metal nanoparticles are preferably selected from one or more of gold nanoparticles (AuNPs), silver nanoparticles (AgNPs) and ferrosoferric oxide nanoparticles.
[0065] The carbon-based light absorbing material is preferably selected from one or more of carbon nanotubes, graphene and carbon black.
[0066] The polymer light absorbing material may be conventional in the art, and is preferably selected from one or more of polydopamine, polypyrrole, and polyaniline.
[0067] The two-dimensional transition metal carbide or carbonitride (Mxene) is preferably Ti 3 C 2 T x .
[0068] In the present invention, optionally, the photothermal layer further comprises a cationic polyelectrolyte, wherein the cationic polyelectrolyte is preferably selected from one or more of polydiallyldimethylammonium chloride (PDDA), polyethyleneimine (PEI) and polyallylamine hydrochloride (PAH).
[0069] Preferably, when the surface of the substance having the photothermal conversion effect has a negative charge, the photothermal layer is (cationic polyelectrolyte / substance having the photothermal conversion effect) n A multilayer film; wherein n represents the number of cycles of "cationic polyelectrolyte / substance having a photothermal conversion effect", and n is an integer, n≥1, such as 2, 3, 4, 5 or 6. When the surface of the substance having a photothermal conversion effect has a negative charge, the substance having a photothermal conversion effect and the cationic polyelectrolyte having a positive charge are alternately deposited to obtain the above multilayer film.
[0070] In certain preferred embodiments, the photothermal layer is (PDDA / Mxene) n Multilayer film. Wherein, n represents the number of cycles of PDDA / Mxene, and n is an integer, n≥1, such as 2, 3, 4, 5 or 6. The (PDDA / Mxene) n The multilayer film has good photothermal effect.
[0071] In some preferred embodiments, the photothermal layer is (PDDA / AuNPs) n wherein n represents the number of cycles of PDDA / AuNPs, and n is an integer, n≥1, such as 2, 3, 4, 5 or 6. The (PDDA / AuNPs) n The multilayer film has good photothermal effect.
[0072] In some preferred embodiments, the photothermal layer is a carbon nanotube layer or a polydopamine layer.
[0073] The present invention further provides a method for preparing the self-cleaning composite coating, which comprises: preparing a photothermal layer on a substrate, and then preparing the self-cleaning coating on the photothermal layer.
[0074] In the present invention, the photothermal layer can be prepared by conventional methods in the art, such as immersion deposition, spray coating, spin coating or blade coating.
[0075] In the present invention, when the photothermal layer is (cationic polyelectrolyte / substance having photothermal conversion effect) n In the case of a multilayer film, the multilayer film can be prepared by alternate immersion deposition.
[0076] In certain preferred embodiments, the photothermal layer is (PDDA / Mxene) n Multilayer film, the (PDDA / Mxene) n The multilayer film can be prepared by alternating immersion deposition, and the specific operation includes: immersing the substrate in a PDDA solution for the first time, taking it out and washing it with water, and then immersing it in a Mxene dispersion for the second time, taking it out and washing it with water, that is, depositing a cycle of PDDA / Mxene multilayer film; repeating the above process n times, (PDDA / Mxene) is obtained. n Multilayer film.
[0077] The concentration of the PDDA solution is preferably 0.1-10 mg / mL, such as 1 mg / mL.
[0078] The solvent in the PDDA solution is preferably water.
[0079] The first soaking time may be more than 1 minute, for example 10 minutes.
[0080] The concentration of the Mxene dispersion is preferably 0.01-10 mg / mL, for example 0.1 mg / mL.
[0081] The solvent in the Mxene dispersion is preferably water.
[0082] The second soaking time may be more than 1 minute, for example 10 minutes.
[0083] Deionized water is preferably used for the water washing.
[0084] In some preferred embodiments, the photothermal layer is (PDDA / AuNPs) n Multilayer film, the (PDDA / AuNPs) n The multilayer film can be prepared by alternating immersion deposition, and the specific operation includes: immersing the substrate in a PDDA solution for the first time, taking it out and washing it with water, and then immersing it in a gold nanoparticle (AuNPs) dispersion for the second time, taking it out and washing it with water, that is, depositing a cycle of PDDA / AuNPs multilayer film; repeating the above process n times, (PDDA / AuNPs) is obtained. n Multilayer film.
[0085] The concentration of the PDDA solution is preferably 0.1-10 mg / mL, such as 1 mg / mL.
[0086] The solvent in the PDDA solution is preferably water.
[0087] The first soaking time may be more than 1 minute, for example 10 minutes.
[0088] The concentration of the Mxene dispersion is preferably 0.01-10 mg / mL, such as 0.1 mg / mL.
[0089] The solvent in the Mxene dispersion is preferably water.
[0090] The second soaking time may be more than 1 minute, for example 10 minutes.
[0091] Deionized water is preferably used for the water washing.
[0092] In some preferred embodiments, the photothermal layer is a carbon nanotube layer, and the carbon nanotube layer can be prepared by spraying. The preferred operation includes: spraying a carbon nanotube dispersion on a substrate and drying.
[0093] Wherein, the concentration of the carbon nanotube dispersion is preferably 0.01-15 mg / mL.
[0094] The solvent of the carbon nanotube dispersion can be any conventional solvent in the art that can disperse carbon nanotubes, such as N-methylpyrrolidone, water or N,N-dimethylacetamide.
[0095] The drying temperature may be 20-200°C, for example 70°C.
[0096] In certain preferred embodiments, the photothermal layer is a polydopamine layer, and the polydopamine layer can be prepared by immersion deposition. The preferred operation includes: immersing the substrate in a polydopamine solution, taking it out and drying it.
[0097] Wherein, the concentration of the polydopamine solution is preferably 0.1-100 mg / mL, such as 2 mg / mL.
[0098] The solvent of the polydopamine solution can be any conventional solvent in the art, such as water.
[0099] The soaking time may be 1 to 10 days, for example 3 days.
[0100] The drying may be natural drying at room temperature, which is generally 20 to 40°C.
[0101] In the method for preparing the self-cleaning composite coating, the substrate is as described above, preferably a glass substrate.
[0102] The present invention also provides an application of the self-cleaning composite coating in deicing, defrosting or dewaxing.
[0103] Since the self-cleaning composite coating includes a substance with a photothermal conversion effect, the surface temperature rises under the irradiation of sunlight, causing the ice, frost or wax accumulated on the surface to melt; then due to the excellent self-cleaning property of the polymer coating, the melted ice, frost or wax will slide off the surface, thereby achieving the purpose of deicing, defrosting or dewaxing.
[0104] The present invention also provides an application of the fluorine-containing methacrylate polymer as a self-cleaning coating in the fields of building materials, power facilities, military equipment, electronic equipment screens or lenses, packaging materials, kitchen and bathroom appliance surfaces, oil pipelines, metal processing or ships.
[0105] On the basis of being in accordance with the common sense in the art, the above-mentioned preferred conditions can be arbitrarily combined to obtain the preferred embodiments of the present invention.
[0106] The reagents and raw materials used in the present invention are commercially available.
[0107] The positive and progressive effects of the present invention are:
[0108] The present invention prepares a fluorine-containing polymer by a free radical polymerization method, and the melting point can be 60-120°C, the decomposition temperature is above 250°C, and the thermal stability is good. The coating made of the fluorine-containing polymer has good light transmittance (the light transmittance of the 20μm coating can be as low as 90%), good mechanical stability, low surface energy, and excellent self-cleaning and self-repairing properties, which verifies the feasibility of preparing a super-lubricant coating based on PFDA. Moreover, since the melting point of the fluorine-containing polymer of the present invention is low, the coating can repair its chemical and physical damage by heating.
[0109] In a preferred embodiment, a p-PFDA-C polymer with low surface energy is prepared, and based on the polymer, a transparent super-slip liquid self-cleaning coating with self-healing properties is prepared on a glass substrate. The coating has a low surface energy, and the surface has "liquid-like" properties. It exhibits self-cleaning ability for liquids with high viscosity and low surface tension. For example, 10 μL of liquids with different surface tensions (18.2-72.1 mN / m) and high viscosity (704 mPa*s) can slide down the surface of the coating at a low inclination angle (<25°) without residue. The coating can repair its chemical and physical damage multiple times by heating, which greatly increases the service life of the coating and reduces the maintenance cost of the coating.
[0110] In order to realize the wide application of super-lubricant self-cleaning coatings on different substrates, a self-cleaning coating with substrate universality was prepared by regulating the modulus of the coating for substrates with different properties.
[0111] In a preferred embodiment, for flexible substrates, a low modulus self-cleaning coating is prepared based on a flexible polymer p-(PFDA-BMA) copolymerized with n-butyl methacrylate (BMA) and PFDA. For rigid substrates, a high modulus self-cleaning coating is prepared based on a polymer p-(PFDA-MA) cross-linked copolymerized with methyl acrylate (MA) and PFDA.
[0112] The above-mentioned coatings exhibit extremely high substrate adhesion on both flexible and rigid substrate surfaces, especially p-(PFDA-BMA). When it is applied to a flexible substrate, the coating will not crack or fall off as the flexible substrate is bent or folded. (The coatings prepared in the current prior art generally have poor toughness. When it is applied to a flexible substrate, the coating is prone to crack or fall off as the flexible substrate is bent or folded).
[0113] The coating surface exhibits "liquid-like" properties that give the coating excellent super-slip self-cleaning properties. Liquids of various surface tensions and viscosities can slide on the above coating at a relatively low sliding angle, for example, the sliding angle of 10μL of n-hexane on the coating is less than 10°, the sliding angle of 10μL of silicone oil on the coating is less than 20°, and the sliding angle of 10μL of glycerol on the coating does not exceed 26°. In addition, the coating has anti-fouling, anti-graffiti and anti-adhesion properties; the self-cleaning property can be restored by heating after oxidative degradation, and the excellent self-cleaning property is still maintained after multiple oxidative degradation-thermal repair.
[0114] The present invention combines the photothermal layer with the self-cleaning coating so that the obtained coating has good photothermal effect, which, combined with the excellent self-cleaning property of the polymer coating, can remove solids that are easily melted under light (such as ice, frost, wax, etc.). BRIEF DESCRIPTION OF THE DRAWINGS
[0115] Figure 1 For p-PFDA-C polymer 1 H-NMR spectrum. Figure 1 b is p-PFDA polymer 1 H-NMR spectrum.
[0116] Figure 2 DSC curves of p-PFDA-C polymer and uncrosslinked p-PFDA polymer (nitrogen atmosphere).
[0117] Figure 3 Figure 3 is the TGA curves of p-PFDA-C polymer and uncrosslinked p-PFDA polymer (nitrogen atmosphere).
[0118] Figure 4 UV-visible spectra of p-PFDA coating and p-PFDA-C coating.
[0119] Figure 5 Graph showing the Young's modulus of the p-PFDA coating and the p-PFDA-C coating versus the indentation depth.
[0120] Figure 6 Static contact angle data of different liquids on p-PFDA-C coating.
[0121] Figure 7 a is the SEM-EDS spectrum of F of p-PFDA-C coating, Figure 7 b is the XPS spectrum of p-PFDA-C coating.
[0122] Figure 8 a is a picture of 20 μL silicone oil trailing sliding on plasma-etched p-PFDA-C coated glass. Figure 8 b is Figure 8A photo of 20 μL of silicone oil sliding off completely after the coating in a was heated on a hot plate at 100°C for 2 minutes.
[0123] Fig. 9 For p-(PFDA-MA) polymer 1 H-NMR spectrum.
[0124] Fig.10 For p-(PFDA-BMA) polymer 1 H-NMR spectrum.
[0125] Fig.11 DSC curves of p-(PFDA-MA) polymer and p-(PFDA-BMA) polymer (nitrogen atmosphere).
[0126] Fig.12 TGA curves of p-(PFDA-MA) and p-(PFDA-BMA) (nitrogen atmosphere).
[0127] Fig.13 Graph showing the Young's modulus of the p-(PFDA-MA) coating and the p-(PFDA-BMA) coating versus the indentation depth.
[0128] Fig.14 The following are photos of coatings prepared by coating p-(PFDA-MA) or p-(PFDA-BMA) on different substrates.
[0129] Fig.15 UV-visible spectra of p-(PFDA-MA) and p-(PFDA-BMA) coatings.
[0130] Fig.16 XRD patterns of p-(PFDA-MA) coating (substrate is glass) and p-(PFDA-BMA) coating (substrate is glass).
[0131] Fig.17 is a micrograph of the p-(PFDA-MA) coating on the glass substrate after the tape test.
[0132] Fig.18 a, Photographs of PET-p-(PFDA-BMA) coating in 18b when twisted or bent; Fig.18 c is the folding photograph of PI-p-(PFDA-BMA) coating.
[0133] Fig.19 This is a photo of 20 μL of red silicone oil dropping on a coated or uncoated glass sheet, stainless steel sheet, PET, or polytetrafluoroethylene sheet tilted at 12°. Fig.19 a~ Fig.19d is a photo of different coatings when silicone oil is just dropped on the coating. Fig.19 a-1~ Fig.19 d-1 are Fig.19 a- Fig.19 b is the photo after the silicone oil slipped off. Fig.19 e~ Fig.19 h is a photograph of the silicone oil sliding onto different uncoated substrates.
[0134] Fig. 20 ai is a photo of uncoated glass painted with a brush dipped in ink. Fig. 20 aii is a photograph of a glass substrate-p-(PFDA-MA) coating coated with an ink-soaked brush.
[0135] Fig. 20 bi is a photo of pure PI painted with a brush dipped in ink, Fig. 20 bii is a photograph of the PI substrate-p-(PFDA-MA) coating coated with a brush dipped in ink.
[0136] Fig. 20 ci is a microscope image of a finger pressing on uncoated glass. Fig. 20 cii is a microscope picture of a finger pressing on glass coated with p-(PFDA-MA) coating.
[0137] Fig. 20 di is a photograph of oil red-dyed glycerin being poured into an uncoated container. Fig. 20 dii is a photograph of Oil Red-dyed glycerol being poured into a container coated with p-(PFDA-MA) coating.
[0138] Fig.21 a is a photo of 20 μL silicone oil sliding on a plasma-etched glass substrate-p-(PFDA-MA) coating, Fig.21 a-1 is a photo of the silicone oil sliding back on after healing at 100°C for 2 minutes. Fig.21 b is a photo of 20 μL silicone oil sliding on a plasma-etched PET substrate-p-(PFDA-BMA) coating. Fig.21 b-1 is a photo of the silicone oil sliding back on after healing at 100°C for 2 minutes.
[0139] Fig. 22 a is the XPS spectrum of glass substrate-p-(PFDA-MA) coating, Fig. 22 b is the XPS spectrum of p-(PFDA-BMA) coating on PET substrate.
[0140] Fig.23 a. Fig.23a-1 are slide photos of 20 μL silicone oil on the cut glass substrate-p-(PFDA-MA) coating and the slide photo after repair, respectively.
[0141] Fig.23 b. Fig.23 b-1 is a micrograph of the cut glass substrate-p-(PFDA-MA) coating before and after healing.
[0142] Fig.23 c. Fig.23 c-1 is a slide photograph of 20 μL silicone oil on the PET substrate-p-(PFDA-BMA) coating after cutting and a slide photograph after heating.
[0143] Fig.23 d. Fig.23 d-1 is a micrograph of the cut PET substrate-p-(PFDA-BMA) coating before and after healing.
[0144] Fig.24 UV-visible spectra of sample MX-SOPS and substrate MX.
[0145] Fig.25 This is a real photo of the sample MX-SOPS.
[0146] Fig.26 The temperature rise (ΔT) of the MX-SOPS surface changes with the irradiation time.
[0147] Fig. 27 a shows the deicing process of sample MX-SOPS under the irradiation of solar simulator.
[0148] Fig. 27 b is a picture of the sample surface taken by an infrared camera after the ice slid off the MX-SOPS surface.
[0149] Fig. 27 c is the defrosting process of sample MX-SOPS under the irradiation of the solar simulator.
[0150] Fig. 27 d is a picture of the sample surface taken by an infrared camera after the frost slid off the MX-SOPS surface.
[0151] Fig.28 The deicing process of the sample MX-SOPS under sunlight in a real environment.
[0152] Fig.29 a shows the process of removing solid wax from sample MX-SOPS under the irradiation of a solar simulator.
[0153] Fig.29 b shows the wax droplet removal process of sample MX-SOPS under the irradiation of solar simulator. DETAILED DESCRIPTION
[0154] The present invention is further described below by way of examples, but the present invention is not limited to the scope of the examples. The experimental methods in the following examples without specifying specific conditions are carried out according to conventional methods and conditions, or selected according to the product specifications.
[0155] The sources of raw materials in the following examples are as follows:
[0156] 2-(Perfluorooctyl)ethyl methacrylate (PFDA), N,N-methylenebisacrylamide (MBAA), methyl acrylate (MA), n-butyl methacrylate (BMA) and N,N-methylenebisacrylamide (MBAA) were purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.
[0157] Azobisisobutyronitrile (AIBN) was purchased from Tianjin Zhiyuan Chemical Reagent Co., Ltd. The purification process of AINB is as follows: add anhydrous ethanol (100 mL) to a 250 mL round-bottom flask, heat it in an oil bath at 75°C until the anhydrous ethanol boils, and then quickly add AIBN (10 g) to the round-bottom flask. After stirring to dissolve, filter the solution with a Buchner funnel while it is hot, collect the filtrate and cool the filtrate to room temperature until crystals occur. The filtrate that produces crystals is allowed to stand for another hour (h) until the crystals are complete, and then filter it with a Buchner funnel. Collect the filter cake and dry it in a natural environment for 12 hours, and finally dry it in a vacuum oven for 12 hours to obtain the purified AIBN. The purified AIBN is placed in a brown bottle and stored at low temperature for later use.
[0158] N,N-Dimethylformamide (DMF), ether, anhydrous ethanol, hexane, acetone, hexadecane, toluene, dimethyl sulfoxide (DMSO), and glycerol were purchased from Beijing Chemical Reagent Company.
[0159] Except for AIBN which required further purification, all chemical reagents were used directly after purchase.
[0160] In the effect embodiment, the specific testing instruments are as follows:
[0161] 1The H NMR spectrum was obtained by testing with a Bruker nuclear magnetic resonance instrument (500MHz AVANCEIII500); the melting point of the polymer was tested by a TA differential scanning calorimeter (DSC204); the thermal stability was tested by a TA company's thermal gravimetric analyzer (TGA Q800); the nanoindentation test of the coating was tested by an Agilent nanoindenter (G200); the UV-visible spectrum of the coating was obtained by testing with a Shimadzu UV spectrophotometer (UV-2700); the atomic force microscopy image (AFM) of the coating was obtained by testing with a Bruker atomic force microscope (Nanoscope IV) in lightweight mode; the scanning electron microscopy image (SEM) of the coating was obtained by testing with a Thermo scanning electron microscope (FEI); the X-ray powder diffraction (XRD) spectrum of the coating was obtained by testing with an Ultima IV was measured by X-ray diffractometer; the wettability of the coating was measured by Kruess contact angle measurement system (DSA10-MK2); the X-ray photoelectron spectroscopy of the coating was measured by R3000 / VUV5K / MX-650XPS / UPS system (PREVAC); the etching treatment of the sample was processed by plasma cleaning instrument (YZD08-5C). Optical pictures were taken by Canon camera (SX40 HS).
[0162] The adhesion test between the coating and the substrate is carried out in accordance with ASTM D3359. First, place the glass coated with the polymer coating on the table, hold the handle of the QFH-type grid knife, make the multi-blade cutting knife (11 blades, 1mm interval) perpendicular to the plane of the sample, and scratch it steadily at a speed of 20mm / s with uniform pressure. Then rotate the sample 90°, and repeat the above operation at the above-cut incision to form a grid pattern. Then use a soft brush to brush forward and backward along the diagonal of the grid pattern five times. Finally, stick the tape on the grid pattern, quickly peel off the tape in a 180° direction, and finally observe the peeling of the coating at the grid pattern under a microscope.
[0163] Example 1 Preparation of cross-linked polymer p-PFDA-C:
[0164] The stirring bar, PFDA (4 g, 7.50 mmol), MBAA (0.011 g, 0.075 mmol) and DMF (16 g) were added to a 100 mL round-bottom flask in sequence, and stirred in an oil bath at 65°C for 30 min to obtain a clear and transparent mixed solution. Then the initiator AIBN (0.04 g) was added to the above mixed solution, and the reaction was continued at 65°C for 24 h. After the reaction, the drug in the round-bottom flask was cooled to room temperature, then poured into ether (200 mL) and stirred for 30 min to remove unreacted monomers, and then filtered and dried thoroughly to obtain pure cross-linked p-PFDA-C polymer (white powder).
[0165] Figure 1 a is p-PFDA-C polymer 1 H-NMR spectrum, where a:b; c; d = 2:2:3:2.
[0166] 1 H-NMR (500MHz, C 2 DF 3 O 2 ,δ):δ=4.77-4.30(2H,-O-CH 2 -CH 2 -), 2.88-2.47(3H, -C-CH 3 ),2.49-1.85(2H,-C-CH 2 -C-), 1.46-1.04(2H, -CF 2 -CH 2 -).
[0167] Solubility: The polymer cannot be dissolved in conventional organic solvents (ethanol, acetone, chloroform, tetrahydrofuran, DMF, DMSO, etc.), but can only be dissolved in trifluoroacetic acid and trifluoroethanol, which lays the foundation for the coating to achieve self-cleaning in a variety of organic solvents.
[0168] Example 2 Preparation of uncrosslinked polymer p-PFDA:
[0169] The preparation method thereof is different from that of Example 1 only in that no cross-linking agent MBAA is added.
[0170] Figure 1 b is p-PFDA polymer 1 H-NMR spectrum.
[0171] 1 H-NMR (500MHz, C 2 DF 3 O 2 ,δ):δ=4.72-4.39(2H,-O-CH 2-CH 2 -), 2.80-2.55(3H, -C-CH 3 ),2.41-2.11(2H,-C-CH 2 -C-), 1.46-1.04(2H, -CF 2 -CH 2 -).
[0172] Example 3
[0173] The p-PFDA coating and p-PFDA-C coating were prepared by solvent-free hot scraping:
[0174] Place a dry glass substrate flat on a 100°C hot plate, and stick a 0.02mm thick tape on the edge of the substrate. Take an appropriate amount of the p-PFDA-C polymer prepared in Example 1 or the p-PFDA polymer prepared in Example 2 and place it on the edge of the substrate. After waiting for 5 minutes for the polymer to melt, place a coating rod (with a diameter of 1 cm) close to the substrate and push it slowly along the edge at a uniform speed until the polymer is evenly covered on the substrate. Finally, the substrate is evenly covered with a layer of polymer coating with the same thickness as the tape, and p-PFDA coating and p-PFDA-C coating are obtained respectively. Since no solvent is used in the preparation of the coating, the thickness of the fixed tape is the thickness of the prepared coating when the coating is prepared.
[0175] Effect Example 1
[0176] The cross-linked p-PFDA-C polymer prepared in Example 1 and the uncross-linked p-PFDA polymer prepared in Example 2 and their coating performance tests:
[0177] 1. Thermal characterization was performed using differential scanning calorimetry and thermogravimetric analysis
[0178] Figure 2 DSC curves of p-PFDA-C polymer and uncrosslinked p-PFDA polymer (nitrogen atmosphere). Figure 2 It can be seen that the p-PFDA-C polymer has an obvious endothermic peak at 88.7° C. The appearance of the endothermic peak indicates that the melting point of the polymer p-PFDA-C is 88.7° C. Compared with the uncrosslinked polymer p-PFDA, the melting point is increased by 4° C.
[0179] Figure 3 Figure 2 is the TGA curve of p-PFDA-C polymer and uncrosslinked p-PFDA polymer (nitrogen atmosphere). Figure 3 It can be seen that the decomposition temperatures of p-PFDA-C (decomposition temperature of 256°C) and p-PFDA polymer (decomposition temperature of 272°C) are both above 250°C, and have excellent thermal stability.
[0180] 2. Transparency
[0181] Generally, fluorine polymers are easy to crystallize, and the phase separation structure formed by crystallization will cause serious scattering of visible light, making the transparency of such polymers worse, such as polytetrafluoroethylene and polyvinylidene fluoride. However, the p-PFDA-C coating prepared by p-PFDA-C polymer has good transparency. Figure 4 shown. Figure 4 The UV-visible spectra of p-PFDA coating and p-PFDA-C coating are shown in Figure 2. Figure 4 It can be seen that the transmittance of the p-PFDA-C coating with a thickness of 20μm is 90%, and the transmittance of the p-PFDA coating with a thickness of 20μm is 92%, and the coating has excellent transparency. Self-cleaning surfaces with high transparency can be applied to protect buildings, solar cells, electronic device screens, lenses, and artwork covers.
[0182] 3. Mechanical performance stability
[0183] The coating made of polymer p-PFDA has poor stability. If the coating is left at room temperature for more than 12 hours, the p-PFDA coating will automatically crack (the cohesive force is too strong and the coating is brittle), making it unusable. However, the coating made of cross-linked polymer p-PFDA-C can be stable for a long time and can be left at room temperature for more than 1 year.
[0184] Figure 5 The graph of Young's modulus of p-PFDA coating and p-PFDA-C coating versus indentation depth. From the nanoindentation curve of the coating, it can be seen that the modulus of p-PFDA-C (0.70GPa) is higher than that of the uncrosslinked p-PFDA coating (0.57GPa). At the same time, the introduction of the crosslinking agent makes the polymer a three-dimensional network with a larger internal force, which improves the stability of the coating.
[0185] 4. Wettability and self-cleaning
[0186] The static contact angle and sliding angle of liquids with different surface tensions on the coating were investigated.
[0187] Figure 6 Figure 2 is the static contact angle data of different liquids on the p-PFDA-C coating. Figure 6It can be seen that with the increase of liquid surface tension, the contact angle of the liquid on the p-PFDA-C coating gradually increases. The contact angles of 4 μL of n-hexane, silicone oil, ethanol, acetone, hexadecane, toluene, DMSO, glycerol and water are 63±1°, 63±1°, 61±1°, 62±3°, 72±1°, 68±3.5°, 89±1°, 107±0.5° and 120±0.5°, respectively. Among them, due to the strong volatility of ethanol, acetone and toluene, their tested contact angles are relatively small.
[0188] The sliding angle of the liquid on the self-cleaning coating is not only related to the surface tension of the liquid, but the viscosity of the liquid is also an important influencing factor. Without considering the influence of the surface tension of the liquid, the higher the viscosity of the liquid, the greater the adhesion between the liquid and the solid surface, and thus the more difficult it is for the liquid to slide on the coating surface. So far, few self-cleaning coatings reported can simultaneously achieve good self-cleaning effects on ultra-low surface tension liquids such as n-hexane (18.2mN / m), ethanol (22.2mN / m), and high viscosity liquids such as silicone oil (20.9mN / m, 100mPa*s), glycerol (62.7mN / m, 704mPa*s). However, this super-slippery liquid self-cleaning coating not only has excellent self-cleaning properties for liquids with extremely low surface energy, but also has unprecedented self-cleaning properties for ultra-high viscosity liquids.
[0189] The sliding angle data of liquids with different viscosities and surface tensions on the p-PFDA-C coating are shown in Table 1. The sliding angles of 10 μL of n-hexane, silicone oil, ethanol, acetone, hexadecane, toluene, DMSO, glycerol and water on the coating are 9°, 17°, 16°, 12°, 10°, 11°, 21°, 25° and 24°, respectively.
[0190] Table 1 Sliding angles of liquids with different viscosities and surface tensions on p-PFDA-C coatings
[0191] 10μL liquid n-Hexane Silicone oil Ethanol acetone Hexadecane Toluene DMSO glycerin water Surface tension mN / m 18.2 20.9 22.3 23.3 27.4 28.5 43.6 62.7 72.1 Viscosity mPa·s 0.31 100 1.10 0.32 2.27 0.59 1.98 704 1.00 Sliding angle° 9° 17° 16° 12° 10° 11° 21° 25° 24°
[0192] For the coating made of polymer p-PFDA, the static contact angle and sliding angle of liquids with different surface tensions on the coating are comparable to those of the coating made of polymer p-PFDA-C.
[0193] 5. Analyze the surface composition of the coating using energy dispersive X-ray analyzer (EDS) and X-ray photoelectron spectroscopy (XPS)
[0194] Figure 7 a is the SEM-EDS spectrum of F of p-PFDA-C coating, Figure 7 b is the XPS spectrum of the p-PFDA-C coating. From the EDS spectrum of the p-PFDA-C coating ( Figure 7 a) The surface of the coating is evenly and uniformly distributed with fluorine elements. The rich fluorine elements on the surface give the coating extremely low surface energy. XPS testing of the coating further proves that the coating surface contains a large amount of fluorine elements. Figure 7 As shown in b, the XPS spectrum of the p-PFDA-C coating has a strong fluorine element signal at 688 eV. Combined with the polymer structure analysis, this is the signal of the fluorine element on the side chain of the p-PFDA-C polymer.
[0195] For the coating made of polymer p-PFDA, its SEM-EDS spectrum and XPS spectrum are comparable to those of the coating made of polymer p-PFDA-C.
[0196] 6. Self-healing
[0197] During actual use, the coating is exposed to the air for a long time. After long-term use, it is easy to be oxidized, causing it to lose its self-cleaning properties. When the p-PFDA-C coating loses its self-cleaning properties due to oxidation, its self-cleaning properties can be repaired by heating. In order to verify the repairability of the p-PFDA-C coating, the process of thermal repair of the p-PFDA-C coating after oxidation was simulated.
[0198] The p-PFDA-C coating was treated with plasma to oxidize its surface to simulate the oxidation condition of the p-PFDA-C coating after long-term use (oxygen plasma treatment, using a YZD08-5C plasma processor (Beijing Huiguang Technology, China), 0.27 mbar, 40 W for three minutes). Figure 8 a is a picture of 20 μL silicone oil trailing sliding on plasma-etched p-PFDA-C coated glass. Figure 8 b is Figure 8 The coating of a was placed on a hot plate at 100°C for 2 minutes, and 20 μL of silicone oil completely slid off. Figure 8 It can be seen from Figure 1 that when silicone oil (20 μL) dyed with oil red is dropped on the plasma-treated coating tilted at 12°, the silicone oil will slide on the coating, but a serious tailing phenomenon occurs, which indicates that the self-cleaning property of the coating is destroyed.
[0199] After the coating was heated on a hot plate at 100°C for 2 minutes, silicone oil was dropped on the coating. The silicone oil slid off the coating completely again without any residue, and the self-cleaning property of the coating was restored ( Figure 8b). This is because when the oxidized p-PFDA-C coating is heated, the polymer chain mobility is greatly enhanced, and the carbon-fluorine side chains inside the coating tend to move toward the surface, increasing the number of carbon-fluorine chains on the coating surface, reducing the surface tension of the coating again, and restoring the self-cleaning performance. After the coating was subjected to 5 cycles of plasma oxidation etching-heat treatment, the coating still maintained good self-cleaning properties, and the sliding angle only increased by 2° compared with the first time.
[0200] The sliding angle data of 10 μL silicone oil on the p-PFDA-C coating after different etching-repair cycles are shown in Table 2 below.
[0201] Table 2
[0202] 0 times 1 time 2 times 3 times 4 times 5 times Sliding angle° 16 15 16 16 17 18
[0203] For the coating made of polymer p-PFDA, its self-healing property is comparable to that of the coating made of polymer p-PFDA-C.
[0204] The polymers prepared in Examples 1-2 can also be applied to other rigid substrates besides glass, such as stainless steel, etc. When applied to other rigid substrate materials, the above properties of the coatings prepared respectively are comparable to those of the coatings prepared on the glass substrate.
[0205] Example 4
[0206] Preparation of copolymer p-(PFDA-MA):
[0207] A stirring bar, PFDA (4 g, 7.5 mmol), MA (0.32 g, 3.75 mmol), MBAA (0.017 g, 0.11 mmol) and DMF (21.6 g) were added to a 100 mL round-bottom flask and stirred in an oil bath at 65°C for 30 minutes (min) to obtain a clear and transparent mixed solution. Then, an initiator AIBN (0.043 g) was added to the mixed solution and the reaction was continued at 65°C for 24 hours (h). After the reaction, a white solid crude product was generated at the bottom of the round-bottom flask. The round-bottom flask was cooled to room temperature, and then the crude product was washed three times with a large amount of ether to remove unreacted monomers. The washed product was thoroughly dried to obtain a pure p-(PFDA-MA) polymer.
[0208] Fig. 9 For p-(PFDA-MA) polymer 1 H-NMR spectrum, where a:b:c:d:e:f=1:3:2:3:2:2.
[0209] 1 H-NMR (500MHz, C 2DF 3 O 2 ,δ):δ=4.77-4.30(2H,-O-CH 2 -CH 2 -),4.03-3.79(3H,O-CH 3 ),2.88-2.47(3H,-C-CH 3 ),2.49-1.85(2H,-CH-CH 2 -C-), 1.46-1.04(2H, -CF 2 -CH 2 -).
[0210] Example 5
[0211] Preparation of copolymer p-(PFDA-BMA):
[0212] Add a stirrer, PFDA (4 g, 7.5 mmol), BMA (0.53 g, 3.75 mmol) and DMF (22.6 g) to a 100 mL round-bottom flask and stir in an oil bath at 65°C for 30 min to obtain a clear and transparent mixed solution. Then add initiator AIBN (0.045 g) to the mixed solution and continue the reaction at 65°C for 24 h. After the reaction is completed, cool the drug in the round-bottom flask to room temperature, then pour it into ether (200 mL) and stir for 30 min to remove unreacted monomers, and then filter and dry thoroughly to obtain pure p-(PFDA-BMA) polymer.
[0213] Fig.10 For p-(PFDA-BMA) polymer 1 H-NMR spectrum. Among them, a+g:b+h:i+c+d:e:f=6:4:6:3:2.
[0214] 1 H-NMR (500MHz, C 2 DF 3 O 2 ,δ):δ=4.72-4.38(2H,-O-CH 2 -CH 2 -), 2.80-2.54(3H, -C-CH 3 ),2.41-2.01(2H,-C-CH 2 -C-), 1.44-1.04(5H, -CF 2 -CH 2 -,-CH 2 -CH 2 -CH 3 ).
[0215] Example 6
[0216] A 0.02 mm p-(PFDA-MA) coating and a 0.02 mm p-(PFDA–BMA) coating were prepared by solvent-free hot scraping. Except for the substrate, the specific preparation method was the same as that of Example 3:
[0217] Using p-(PFDA-MA) polymer, 0.02 mm self-cleaning coatings were prepared on glass and stainless steel substrates, respectively.
[0218] Using p-(PFDA-BMA) polymer, 0.02 mm self-cleaning coatings were prepared on PET, PI and Teflon substrates respectively.
[0219] Effect Example 2
[0220] The cross-linked p-(PFDA-MA) polymer prepared in Example 4 and the uncross-linked p-(PFDA-BMA) polymer prepared in Example 5 and their coating performance tests:
[0221] 1. Thermal characterization was performed using differential scanning calorimetry and thermogravimetric analysis
[0222] Fig.11 DSC curves of p-(PFDA-MA) polymer and p-(PFDA-BMA) polymer (nitrogen atmosphere). Fig.11 It can be seen that the polymers p-(PFDA-MA) and p-(PFDA-BMA) have obvious endothermic peaks at 85.9°C and 72.1°C, respectively, indicating that the melting points of the polymers p-(PFDA-MA) and p-(PFDA-BMA) are 85.9°C and 72.1°C, respectively.
[0223] Fig.12 The TGA curves of p-(PFDA-MA) and p-(PFDA-BMA) (nitrogen atmosphere) are shown in the figure. From the TGA curves, the decomposition temperatures of the polymers p-(PFDA-MA) (decomposition temperature is 278°C) and p-(PFDA-BMA) (decomposition temperature is 276°C) are both above 270°C, which indicates that they have excellent thermal stability. In summary, both polymers have excellent thermal processability.
[0224] 2. Universality and transparency of substrates for self-cleaning coatings
[0225] Fig.13 The graph of Young's modulus of p-(PFDA-MA) coating and p-(PFDA-BMA) coating versus indentation depth. From the nanoindentation curve of the coating, it can be seen that the modulus of p-(PFDA-MA) coating is 1.42 GPa, and the modulus of p-(PFDA-BMA) coating is 0.49 GPa.
[0226] Fig.14 The following are photos of coatings made by coating p-(PFDA-MA) or p-(PFDA-BMA) on different substrates. For rigid substrates (glass and stainless steel sheets), a polymer p-(PFDA-MA) with a larger modulus (1.42 GPa) was used to prepare the coatings. For flexible substrates (PET, Teflon, and PI), a polymer p-(PFDA-BMA) with a smaller modulus (0.49 GPa) was used to prepare the coatings. The thickness of the coatings was 0.02 mm.
[0227] like Fig.14 As shown, the coating can be applied on glass, stainless steel, PET, Teflon, PI, and has good transparency (the transmittance of the coating has nothing to do with the type of substrate, but only with the material and thickness of the coating). The transmittance of p-(PFDA-MA) and p-(PFDA-BMA) coatings with a thickness of 20 μm is 90% and 94% respectively ( Fig.15 ).
[0228] Fig.16 The XRD patterns of p-(PFDA-MA) coating (substrate is glass) and p-(PFDA-BMA) coating (substrate is glass). Fig.16 It can be seen that there are crystals inside the p-(PFDA-MA) coating and the p-(PFDA-BMA) coating, and the crystal size is small.
[0229] Fig.17 Figure 2 is a micrograph of the p-(PFDA-MA) coating on a glass substrate after the tape test. Fig.17 As shown in the figure, after the cross-cut-tape method test, the p-(PFDA-MA) coating coated on the rigid substrate-glass has a relatively smooth cut edge and the coating has almost no peeling. It is determined that the p-(PFDA-MA) coating has a 5B adhesion grade to the glass substrate. For flexible substrates, the prepared p-(PFDA-BMA) coating is highly flexible and stretchable. Fig.18 As shown ( Fig.18 a, Photographs of PET-p-(PFDA-BMA) coating in 18b when twisted or bent; Fig.18 c is a folded photograph of the PI-p-(PFDA-BMA) coating. The coating will not be damaged when the flexible substrate coated with the p-(PFDA-BMA) coating is bent, twisted and folded.
[0230] 4. Wettability and self-cleaning properties of the coating
[0231] The static contact angle and sliding angle of liquids with different surface tensions on the coating were investigated.
[0232] As shown in the table, as the surface tension of the liquid increases, the contact angle of the liquid on the p-(PFDA-MA) and p-(PFDA-BMA) coatings gradually increases. The contact angles of 4 μL of n-hexane, silicone oil, ethanol, acetone, hexadecane, toluene, DMSO, glycerol and water on the p-(PFDA-MA) coating are 55°, 63°, 64°, 67°, 76°, 74°, 89°, 108° and 120°, respectively. The contact angles of 4 μL of n-hexane, silicone oil, ethanol, acetone, hexadecane, toluene, DMSO, glycerol and water on the p-(PFDABMA) coating are 63°, 63°, 61°, 62°, 72°, 68°, 89°, 107° and 120°, respectively. Among them, the contact angles of ethanol and toluene are relatively small because of their strong volatility.
[0233] Generally, the static contact angle alone cannot reflect the actual wettability of the material, and the sliding angle can more accurately characterize the wettability of the solid surface. The sliding angle of the liquid on the self-cleaning coating is not only related to the surface tension of the liquid, but the viscosity of the liquid is also a very important influencing factor. Without considering the influence of the surface tension of the liquid, the higher the viscosity of the liquid, the more difficult it is for the liquid to slide on the coating surface. So far, there are few self-cleaning coatings that can simultaneously have a good self-cleaning effect on ultra-low surface tension liquids such as n-hexane (18.2mN / m), ethanol (22.2mN / m), and high viscosity liquids such as silicone oil (20.9mN / m, 100mPa*s), glycerol (62.7mN / m, 704mPa*s). However, the prepared super-slippery liquid self-cleaning coating not only has excellent self-cleaning properties for liquids with extremely low surface energy, but also has unprecedented self-cleaning properties for ultra-high viscosity liquids.
[0234] As shown in the table, the sliding angles of 10 μL of n-hexane (18.2 mN / m), silicone oil (20.9 mN / m), ethanol (22.3 mN / m), acetone (23.3 mN / m), hexadecane (27.4 mN / m), toluene (28.5 mN / m), DMSO (43.6 mN / m), glycerol (62.7 mN / m), and water (72.1 mN / m) on the p-(PFDA-MA) coating were 8°, 17°, 15°, 12°, 8°, 11°, 20°, 25°, and 23°, respectively. °; 10μL of n-hexane (18.2mN / m), silicone oil (20.9mN / m), ethanol (22.3mN / m), acetone (23.3mN / m), hexadecane (27.4mN / m), toluene (28.5mN / m), DMSO (43.6mN / m), glycerol (62.7mN / m) and water (72.1mN / m) on the p-(PFDA-BMA) coating have sliding angles of 10°, 17°, 16°, 13°, 9°, 11°, 21°, 26° and 24°, respectively. Although the contact angles of most liquids on the coating surface are less than 90°, their sliding angles are relatively low because the perfluorocarbon chains on the coating surface are highly mobile.
[0235] The contact angle or sliding angle data of liquids with different viscosities and surface tensions on the p-(PFDA-MA) coating or p-(PFDA-BMA) are shown in Table 3.
[0236] Table 3
[0237]
[0238]
[0239] Self-cleaning performance demonstration 1:
[0240] Thanks to the excellent super-lubricant self-cleaning performance of the coating, the coating can prevent oil stains on surfaces such as glass, metal, PET, and polytetrafluoroethylene, which proves the excellent anti-fouling performance of the coating.
[0241] like Fig.19 As shown ( Fig.19 a~ Fig.19 d is a photo of different coatings when silicone oil is just dropped on the coating. Fig.19 a-1~ Fig.19 d-1 are Fig.19 a- Fig.19 b is the photo after the silicone oil slipped off. Fig.19 e~ Fig.19h is a photograph of silicone oil sliding off on different uncoated substrates. When 20 μL of silicone oil with a surface tension of 20.9 mN / m and a viscosity of 100 mPa*s, which was dyed with oil red, was dropped on a coated glass sheet, stainless steel sheet, PET, and polytetrafluoroethylene sheet tilted at 12°, the silicone oil can slide off easily without any residue. On the contrary, 20 μL of silicone oil completely spread on the uncoated glass sheet, stainless steel sheet, PET, and polytetrafluoroethylene sheet. Even polytetrafluoroethylene, which is generally regarded as a "non-stick coating and easy-to-clean material", is contaminated by silicone oil with low surface tension and high viscosity. The extremely low surface tension of the coating surface of the present invention makes the coating surface exhibit "liquid-like" properties. It is precisely because of its "liquid-like" properties that the coating exhibits self-cleaning properties based on the properties of super-slippery liquids for liquids with extremely low surface tension and extremely high viscosity.
[0242] It should be noted that Fig.19 In the present invention, (1) p-(PFDA-MA) polymer was used to prepare the self-cleaning coating on glass and stainless steel substrates, and p-(PFDA-BMA) polymer was used to prepare the self-cleaning coating on PET and Teflon substrates; (2) the liquid used was 20 μL of oil red-dyed silicone oil.
[0243] Self-cleaning performance demonstration 2:
[0244] Since both water and oil can slide on the surface of the coating, the coating exhibits excellent anti-graffiti and anti-adhesion capabilities in practical applications.
[0245] Fig. 20 ai is a photo of uncoated glass painted with a brush dipped in ink. Fig. 20 aii is a photograph of a glass substrate-p-(PFDA-MA) coating coated with a brush dipped in ink. Fig. 20 bi is a photo of pure PI painted with a brush dipped in ink, Fig. 20 Figure bii is a photo of the PI substrate-p-(PFDA-MA) coating coated with an ink brush. As shown in the figure, when a brush dipped in black ink is brushed on the coated glass and PI, the black ink does not leave any traces on the glass and PI. When a brush dipped in black ink is brushed on pure glass or PI, large pieces of ink are stained on the glass.
[0246] Fig. 20 ci is a microscope image of a finger pressing on uncoated glass. Fig. 20cii is a microscope image of a finger pressing on glass coated with p-(PFDA-MA) coating. From the microscope image, when a finger is pressed on glass coated with p-(PFDA-MA) coating, no trace of fingerprint is left on the coating. In contrast, when a fingerprint is pressed on pure glass, an obvious fingerprint is left on the glass. This is because the surface of the coating of the present invention shows a "liquid-like" property, which makes the surface not wetted by ink or sweat.
[0247] Fig. 20 di is a photograph of oil red-dyed glycerin being poured into an uncoated container. Fig. 20 Figure dii is a photograph of oil red-stained glycerol being poured into a container coated with a p-(PFDA-MA) coating. When the oil red-stained glycerol is poured from a container coated with a p-(PFDA-MA) coating, no glycerol remains in the container, while a large amount of glycerol remains at the bottom of the unmodified container.
[0248] 5. Demonstration of self-healing performance of coating
[0249] During actual use, the coating is exposed to the air for a long time and is easily oxidized, causing it to lose its self-cleaning property. When the prepared p-(PFDA-MA) and p-(PFDA-BMA) coatings lose their self-cleaning properties due to oxidation, their self-cleaning properties can be repaired by heating. In order to verify the repairability of p-(PFDA-MA) and p-(PFDA-BMA) coatings, the process of thermal repair of p-(PFDA-MA) and p-(PFDA-BMA) coatings after oxidation was simulated.
[0250] (1) Chemical etching:
[0251] The p-(PFDAMA) and p-(PFDA-BMA) coatings were oxidized by plasma treatment to simulate the oxidation of glass substrate-p-(PFDA-MA) and PET substrate-p-(PFDA-BMA) coatings after long-term use.
[0252] Fig.21 a is a photo of 20 μL silicone oil sliding on a plasma-etched glass substrate-p-(PFDA-MA) coating, Fig.21 a-1 is a photo of the silicone oil sliding back on after healing at 100°C for 2 minutes. Fig.21 b is a photo of 20 μL silicone oil sliding on a plasma-etched PET substrate-p-(PFDA-BMA) coating. Fig.21 b-1 is a photo of the silicone oil sliding back on after healing at 100°C for 2 minutes.
[0253] As can be seen from the figure, when the oil red-dyed silicone oil is dropped on the plasma-treated coating tilted at 12°, the silicone oil will slide on the coating, but there is a serious tailing phenomenon, which shows that the self-cleaning property of the coating is destroyed. After the coating is heated on a hot plate at 100°C for 2 minutes, the silicone oil is dropped on the coating again, and the silicone oil slides off the coating completely again without any residue, indicating that the self-cleaning property of the coating is restored.
[0254] After the p-(PFDA-MA) and p-(PFDA-BMA) coatings were subjected to 8 plasma oxidation etching-heat treatment cycles, the coatings still maintained good self-cleaning properties, and the sliding angle increased by only 2° compared with the first time. After the coatings were subjected to 8 plasma etching-heat treatment cycles, the coatings still maintained good self-cleaning properties, and the sliding angle increased by only 2° compared with the first time.
[0255] XPS spectra of the coating after 8 cycles of plasma etching and heat treatment ( Fig. 22 a is the XPS spectrum of glass substrate-p-(PFDA-MA) coating, Fig. 22 (b is the XPS spectrum of the p-(PFDA-BMA) coating on the PET substrate). The XPS spectrum of the coating has a strong fluorine signal at 688 eV. Combined with the polymer structure analysis, this is the signal of the fluorine element on the side chain of the p-(PFDA-MA) or p-(PFDA-BMA) polymer. In other words, there is still abundant fluorine on the surface of the coating, which confirms the self-healing performance of the coating.
[0256] After different etching-repair cycles of glass substrate-p-(PFDA-MA) and PET substrate-p-(PFDA-BMA) coatings, the sliding angle data of 10 μL silicone oil on p-(PFDA-MA) and p-(PFDA-BMA) coatings are shown in Table 4.
[0257] Table 4
[0258]
[0259] (2) Scratches:
[0260] In addition to chemical damage, coatings are often unusable due to physical damage during use. Because p-(PFDA-MA) and p-(PFDA-BMA) coatings have a more suitable melting point, when they are physically damaged, they can be repaired by heating the polymer to melt it. In order to verify the repairability of p-(PFDA-MA) and p-(PFDA-BMA) coatings to physical damage, Fig.23As shown in the figure, a scratch of about 70 μm was made on the coating with a surgical blade, and then it was placed on a hot plate at 100°C for 10 minutes, and the scratch was completely repaired. This result proves the excellent self-healing property of the coating.
[0261] Fig.23 a. Fig.23 a-1 are slide photos of 20 μL silicone oil on the cut glass substrate-p-(PFDA-MA) coating and the slide photo after repair, respectively. Fig.23 b. Fig.23 b-1 is a micrograph of the cut glass substrate-p-(PFDA-MA) coating before and after healing.
[0262] Fig.23 c. Fig.23 c-1 is a slide photograph of 20 μL silicone oil on the PET substrate-p-(PFDA-BMA) coating after cutting and a slide photograph after heating. Fig.23 d. Fig.23 d-1 is a micrograph of the cut PET substrate-p-(PFDA-BMA) coating before and after healing.
[0263] Example 7
[0264] The dried glass substrate was immersed in 1 mg / mL PDDA solution for 10 min, and then rinsed thoroughly with deionized water; then, the substrate was immersed in 0.1 mg / mL Ti 3 C 2 T x The PDDA / Mxene multilayer film was prepared by immersing the film in the Mxene dispersion for 10 min and then thoroughly rinsing it with deionized water. The PDDA / Mxene multilayer film was obtained by repeating the above process 4 times. 4 The glass substrate of the multilayer film is denoted as substrate MX.
[0265] The substrate MX was placed flat on a 100°C hot plate, and a 0.01 mm thick tape was attached to the edge of the substrate MX. An appropriate amount of the polymer p-(PFDA-BMA) in Example 5 was placed on the edge of the substrate MX, and the polymer was melted after 5 minutes. A coating rod (1 cm in diameter) was placed close to the substrate MX and slowly pushed along the edge at a uniform speed, and the polymer was evenly covered on the substrate MX. Finally, the substrate MX was evenly covered with a layer of polymer coating with the same thickness as the tape, and the obtained sample was named MX-SOPS.
[0266] Effect Example 3
[0267] Performance test of the sample MX-SOPS prepared in Example 7:
[0268] 1. Transparency
[0269] Fig.24 The UV-visible spectra of the sample MX-SOPS and the substrate MX are shown in Figure 2. Fig.24 It can be seen that the deposition is (PDDA / Mxene) 4 The transmittance of the substrate MX of the multilayer film is 71.4%, while the transmittance of the sample MX-SOPS further having a p-(PFDA-BMA) coating layer with a thickness of 10 μm is 77.3%. Fig.25 This is a real photo of the sample MX-SOPS with the surrounding environment as the background. It can be seen with the naked eye that the sample MX-SOPS has high transparency.
[0270] 2. Photothermal effect
[0271] The sample MX-SOPS was exposed to a solar simulator (a xenon lamp with a standard AM-1.5 spectrum filter and a light intensity of 1.0 kW / m 2 ) irradiated, and the temperature of the sample surface was monitored and recorded by an infrared camera. Fig.26 The temperature rise (ΔT) of the sample surface changes with the irradiation time. Under one sun intensity, the sample surface temperature can rise by 27-31°C, which shows that the sample has a good photothermal effect.
[0272] 3. Self-cleaning
[0273] Self-cleaning performance demonstration 1: De-icing or frost using photothermal effect and self-cleaning properties
[0274] (1) In an environment of -20°C, the surface of the sample MX-SOPS was covered with ice, and then the sample MX-SOPS was exposed to a solar simulator (a xenon lamp light source with a standard AM-1.5 spectrum filter and a light intensity of 1.0 kW / m 2 ) under the irradiation of sunlight, because the sample MX-SOPS has a good photothermal effect, under the irradiation of sunlight, the surface temperature of the sample rises, causing the ice to melt; then due to the excellent self-cleaning property of the polymer coating, the melted ice will slide off the surface of the sample, thus achieving the purpose of deicing. Fig. 27 As shown in a, Fig. 27 b is a picture of the sample surface taken by an infrared camera after the ice slid off the sample surface.
[0275] (2) In an environment of -20°C, the surface of the sample MX-SOPS was covered with frost, and then the sample MX-SOPS was exposed to a solar simulator (a xenon lamp light source with a standard AM-1.5 spectrum filter and a light intensity of 1.0 kW / m 2) under the irradiation of sunlight, because the sample MX-SOPS has a good photothermal effect, under the irradiation of sunlight, the surface temperature of the sample rises, causing the frost to melt; then due to the excellent self-cleaning property of the polymer coating, the melted frost will slide off the surface of the sample, thus achieving the purpose of defrosting. Fig. 27 As shown in c, Fig. 27 d is a picture of the sample surface taken by an infrared camera after the frost slid off the sample surface.
[0276] (3) In a real environment, at 11:30 on December 8, 2020, the MX-SOPS sample with a large amount of frozen ice on its surface was placed outdoors and exposed to sunlight. After being irradiated by sunlight, the surface temperature of the sample rose, causing the ice at the interface between the sample and the surface of the sample to melt; then, due to the excellent self-cleaning property of the polymer coating, the semi-melted ice would slide off the surface of the sample, thus achieving the purpose of deicing. This process is as follows Fig.28 shown.
[0277] Self-cleaning performance demonstration 2: wax removal using photothermal effect and self-cleaning properties
[0278] like Fig.29 As shown in a, at room temperature (25°C), a melted candle is dripped onto the surface of the sample MX-SOPS. The melted wax droplets will solidify firmly on the surface of the sample. The sample is then exposed to a solar simulator (a xenon light source with a standard AM-1.5 spectrum filter and a light intensity of 1.0 kW / m 2 ) under the irradiation of sunlight, because MX-SOPS has a good photothermal effect, under the irradiation of sunlight, the surface temperature of the sample rises, causing the wax to melt. Then, due to the excellent self-cleaning property of the polymer coating, the melted wax will slide off the surface of the sample, thus achieving the purpose of wax removal.
[0279] like Fig.29 As shown in b, at room temperature (25°C), the MX-SOPS sample was exposed to a solar simulator (a xenon lamp light source with a standard AM-1.5 spectrum filter and a light intensity of 1.0 kW / m 2 ) and after irradiation for 10 minutes, the sample surface temperature rises to 56°C under sunlight because MX-SOPS has a good photothermal effect. Then the melted candle is dripped on the surface of MX-SOPS. Due to the high surface temperature, the wax droplets will not solidify on the surface. At the same time, due to the excellent self-cleaning property of the polymer coating, the wax droplets will slide off the sample surface, thereby achieving the purpose of wax removal.
[0280] Example 8
[0281] The dried glass substrate was immersed in a 1 mg / mL PDDA solution for 10 min, and then rinsed thoroughly with deionized water; then, the substrate was immersed in a 0.1 mg / mL gold nanoparticle (AuNPs) dispersion for 10 min, and also rinsed thoroughly with deionized water, thus obtaining a period of PDDA / AuNPs multilayer film. The above process was repeated 4 times to prepare a PDDA / AuNPs multilayer film. 4 Glass substrate AU of multilayer film.
[0282] Place the above substrate AU flat on a 100°C hot plate, and stick a 0.01mm thick tape on the edge of the substrate AU. Take an appropriate amount of the polymer p-(PFDA-BMA) in Example 5 and place it on the edge of the substrate AU. After waiting for 5 minutes, the polymer melts. Place a coating rod (1 cm in diameter) close to the substrate AU and push it slowly along the edge at a uniform speed. The polymer is evenly covered on the substrate AU. Finally, the substrate AU is evenly covered with a layer of polymer coating with the same thickness as the tape. The obtained sample is named AU-SOPS. Since gold nanoparticles have a good photothermal effect, in an environment of minus 15°C, under the irradiation of sunlight, the surface temperature of the sample rises, which will melt the ice or wax accumulated on its surface. Then, due to the excellent self-cleaning property of the polymer coating, the melted ice or wax will slide off the surface of the sample, thereby achieving the purpose of deicing or dewaxing.
[0283] Example 9
[0284] The N-methylpyrrolidone dispersion of carbon nanotubes (0.1 mg / mL) was sprayed on a cleaned glass substrate, which was then placed on a hot plate at 70° C. to be thoroughly dried, and was recorded as substrate CN.
[0285] The above substrate CN was placed flat on a 100°C hot plate, and a 0.01mm thick tape was attached to the edge of the substrate CN. An appropriate amount of the polymer p-(PFDA-BMA) in Example 5 was placed on the edge of the substrate CN. After waiting for 5 minutes for the polymer to melt, a coating rod (1 cm in diameter) was placed close to the substrate AU and slowly pushed along the edge at a uniform speed. The polymer was evenly covered on the substrate CN. Finally, the substrate CN was evenly covered with a layer of polymer coating with the same thickness as the tape. The obtained sample was named CN-SOPS.
[0286] Since carbon nanotubes have a good photothermal effect, in an environment of -50°C, under the irradiation of sunlight, the surface temperature of the sample rises, which will melt the ice, frost or wax accumulated on the surface. Then, due to the excellent self-cleaning property of the polymer coating, the melted ice, frost or wax will slide off the surface of the sample, thus achieving the purpose of de-icing, de-frosting or de-waxing.
[0287] Example 10
[0288] The cleaned glass substrate was immersed in a polydopamine aqueous solution (2 mg / mL) for 3 days, taken out and dried naturally at room temperature, and recorded as substrate PD.
[0289] The substrate PD was placed flat on a 100°C hot plate, and a 0.01 mm thick tape was attached to the edge of the substrate PD. An appropriate amount of the polymer p-(PFDA-BMA) in Example 5 was placed on the edge of the substrate PD, and the polymer was melted after 5 minutes. A coating rod (1 cm in diameter) was placed close to the substrate AU and slowly pushed along the edge at a uniform speed, and the polymer was evenly covered on the substrate PD. Finally, the substrate PD was evenly covered with a layer of polymer coating with the same thickness as the tape, and the obtained sample was named PD-SOPS.
[0290] Since polydopamine has a good photothermal effect, in an environment of -10°C, under the irradiation of sunlight, the surface temperature of the sample rises, which will melt the ice, frost or wax accumulated on the surface. Then, due to the excellent self-cleaning property of the polymer coating, the melted ice, frost or wax will slide off the surface of the sample, thus achieving the purpose of deicing, defrosting or dewaxing.
Claims
1. A method for preparing a fluorine-containing methacrylate polymer, characterized in that: The raw materials of the fluorine-containing methacrylate polymer include polymerization monomers, initiators and solvents; The polymerizable monomer is monomer A, or monomer A and monomer B; monomer A is 2-(perfluorooctyl)ethyl methacrylate; monomer B includes one or more of methyl acrylate, methyl methacrylate, styrene, methoxyethyl acrylate and n-butyl methacrylate; After initiation by the initiator, the polymerizable monomer is subjected to solution polymerization to obtain the fluorine-containing methacrylate polymer; wherein the polymerizable monomer accounts for 1 to 50% of the total mass of the polymerizable monomer and the solvent; When the polymerizable monomers are the monomer A and the monomer B, the molar ratio of the monomer A to the monomer B is 1.5:1 or more; The solvent is N,N-dimethylformamide; The raw materials include a cross-linking agent; The amount of the cross-linking agent is 0-5% of the molar amount of the polymerized monomer, excluding 0%.
2. The method for preparing a fluorine-containing methacrylate polymer according to claim 1, wherein: The amount of the initiator is 0.1-10% of the mass of the polymerization monomer; And / or, the initiator is azobisisobutyronitrile and / or dimethyl azobisisobutyrate.
3. The method for preparing a fluorine-containing methacrylate polymer according to claim 2, wherein: The amount of the initiator is 0.5-1.5% of the mass of the polymerization monomer; And / or, the initiator is purified by recrystallization; And / or, the cross-linking agent is N,N-methylenebisacrylamide.
4. The method for preparing a fluorine-containing methacrylate polymer according to claim 3, characterized in that: The amount of the initiator is 1% of the mass of the polymerization monomer; And / or, the amount of the cross-linking agent is 0-1% of the molar amount of the polymerized monomer, excluding 0%.
5. The method for preparing a fluorine-containing methacrylate polymer according to claim 1, wherein: The monomer B is the methyl acrylate, the methyl methacrylate, the styrene, the methoxyethyl acrylate or the n-butyl methacrylate.
6. The method for preparing a fluorine-containing methacrylate polymer according to claim 5, characterized in that: When the polymerizable monomers are the monomer A and the monomer B, the molar ratio of the monomer A to the monomer B is 2:1, 4:1, 5:1, 8:1 or 10:1; The monomer B is the methyl acrylate or the n-butyl methacrylate.
7. The method for preparing a fluorine-containing methacrylate polymer according to claim 1, characterized in that: The polymerizable monomers are the 2-(perfluorooctyl)ethyl methacrylate and the methyl acrylate; When the polymerizable monomers are the 2-(perfluorooctyl)ethyl methacrylate and the methyl acrylate, the molar ratio of the 2-(perfluorooctyl)ethyl methacrylate to the methyl acrylate is 2:1, 4:1 or 5:1; and / or, the polymerizable monomers are the 2-(perfluorooctyl)ethyl methacrylate and the n-butyl methacrylate; When the polymerizable monomers are the 2-(perfluorooctyl)ethyl methacrylate and the n-butyl methacrylate, the molar ratio of the 2-(perfluorooctyl)ethyl methacrylate to the n-butyl methacrylate is 2:1, 4:1 or 5:
1.
8. The method for preparing a fluorine-containing methacrylate polymer according to claim 1, characterized in that: The initiator is added into the mixed solution containing the polymerization monomer to carry out the solution polymerization.
9. The method for preparing a fluorine-containing methacrylate polymer according to claim 8, characterized in that: The mixed solution is obtained by heating and stirring.
10. The method for preparing a fluorine-containing methacrylate polymer according to claim 9, wherein The heating and stirring temperature is 60-70° C.; the heating and stirring time is 0.2-1 h.
11. The method for preparing a fluorine-containing methacrylate polymer according to claim 10, wherein: The heating and stirring temperature is 65° C.; the heating and stirring time is 0.5 h.
12. The method for preparing a fluorine-containing methacrylate polymer according to claim 1, wherein: The temperature of the solution polymerization is 60-70°C; And / or, the solution polymerization time is 20 to 30 hours; and / or, the polymerizable monomer accounts for 5-45% of the total mass of the polymerizable monomer and the solvent; And / or, the reaction solution after the solution polymerization is post-treated.
13. The method for preparing a fluorine-containing methacrylate polymer according to claim 12, characterized in that: The temperature of the solution polymerization is 62-68°C; And / or, the solution polymerization time is 24 h; and / or, the polymerizable monomer accounts for 10-30% of the total mass of the polymerizable monomer and the solvent; And / or, the post-treatment operations include: cooling, washing, filtering, and drying the obtained filter cake.
14. The method for preparing a fluorine-containing methacrylate polymer according to claim 13, wherein: The temperature of the solution polymerization is 65°C; And / or, the polymerized monomer accounts for 16.7-20% of the total mass of the polymerized monomer and the solvent.
15. A fluorine-containing methacrylate polymer obtained by the method for preparing a fluorine-containing methacrylate polymer according to any one of claims 1 to 14.
16. A self-cleaning coating, characterized in that: The raw material is the fluorine-containing methyl acrylate polymer as claimed in claim 15.
17. The self-cleaning coating according to claim 16, wherein The thickness of the self-cleaning coating is 0.005-0.1 mm.
18. The self-cleaning coating according to claim 17, wherein The thickness of the self-cleaning coating is 0.02-0.06 mm.
19. A method for preparing a self-cleaning coating according to any one of claims 16 to 18, characterized in that: The method comprises the following steps: applying the melted fluorine-containing methacrylate polymer on the substrate by scraping to a desired thickness; The substrate is a rigid substrate or a flexible substrate.
20. The method for preparing a self-cleaning coating according to claim 19, characterized in that: The rigid substrate is glass or stainless steel; The flexible substrate is PET, PI or Teflon; The substrate is placed on a heating platform and heated to a temperature 10° C. above the melting point of the fluorinated methacrylate polymer.
21. The method for preparing a self-cleaning coating according to claim 20, characterized in that: When the polymerizable monomer of the fluorine-containing methacrylate polymer is only the monomer A, or is the monomer A and the methyl acrylate, the substrate is a rigid substrate; When the polymerized monomers of the fluorine-containing methacrylate polymer are the monomer A and n-butyl methacrylate, the substrate is a flexible substrate.
22. Use of the fluorine-containing methacrylate polymer as claimed in claim 15 as a self-cleaning coating in the fields of building materials, power facilities, military equipment, electronic equipment screens or lenses, packaging materials, kitchen and bathroom appliance surfaces, oil pipelines, metal processing or ships.
23. A self-cleaning composite coating, comprising a photothermal layer and a self-cleaning coating, wherein: The photothermal layer includes a substance having a photothermal conversion effect; The self-cleaning coating raw material is a fluorine-containing methyl acrylate polymer prepared by the following method; The method for preparing the fluorine-containing methacrylate polymer, wherein the raw materials of the fluorine-containing methacrylate polymer include polymerization monomers, initiators and solvents; The polymerizable monomer is monomer A, or monomer A and monomer B; monomer A is 2-(perfluorooctyl)ethyl methacrylate; monomer B includes one or more of methyl acrylate, methyl methacrylate, styrene, methoxyethyl acrylate and n-butyl methacrylate; After initiation by the initiator, the polymerizable monomer is subjected to solution polymerization to obtain the fluorine-containing methacrylate polymer; wherein the polymerizable monomer accounts for 1 to 50% of the total mass of the polymerizable monomer and the solvent; When the polymerizable monomers are the monomer A and the monomer B, the molar ratio of the monomer A to the monomer B is at least 0.5:1; When the polymerizable monomer is only the monomer A, the raw material further includes a cross-linking agent.
24. The self-cleaning composite coating according to claim 23, characterized in that The substance having the light-to-heat conversion effect is selected from one or more of the following substances: metal nanoparticles, carbon-based light-absorbing materials, polymer light-absorbing materials, and two-dimensional transition metal carbides or carbonitrides.
25. The self-cleaning composite coating according to claim 24, characterized in that The metal nanoparticles are selected from one or more of gold nanoparticles, silver nanoparticles and ferroferric oxide nanoparticles; The carbon-based light absorbing material is selected from one or more of carbon nanotubes, graphene and carbon black; The polymer light absorbing material is selected from one or more of polydopamine, polypyrrole, and polyaniline; The two-dimensional transition metal carbide or carbonitride is Ti3C2T x .
26. The self-cleaning composite coating according to claim 23, characterized in that The photothermal layer also includes a cationic polyelectrolyte.
27. The self-cleaning composite coating according to claim 26, characterized in that The cationic polyelectrolyte is selected from one or more of polydiallyldimethylammonium chloride, polyethyleneimine and polyallylamine hydrochloride.
28. The self-cleaning composite coating of claim 26, wherein: When the surface of the substance having the photothermal conversion effect has a negative charge, the photothermal layer is (cationic polyelectrolyte / substance having the photothermal conversion effect) n Multilayer film; wherein n represents the number of cycles of cationic polyelectrolyte / substance having light-to-heat conversion effect, n is an integer, n≥1.
29. The self-cleaning composite coating according to claim 28, characterized in that When the surface of the substance having the photothermal conversion effect has a negative charge, the photothermal layer is (cationic polyelectrolyte / substance having the photothermal conversion effect) n Multilayer film; wherein n represents the number of cycles of cationic polyelectrolyte / substance having light-to-heat conversion effect, and n is 2, 3, 4, 5 or 6.
30. The self-cleaning composite coating according to claim 29, characterized in that The photothermal layer is (PDDA / Mxene) n Multilayer film or (PDDA / AuNPs) n Multilayer film.
31. The self-cleaning composite coating of claim 23, wherein: The photothermal layer is a carbon nanotube layer or a polydopamine layer.
32. The self-cleaning composite coating of claim 23, wherein: The amount of the initiator is 0.1-10% of the mass of the polymerization monomer; And / or, the initiator is azobisisobutyronitrile and / or dimethyl azobisisobutyrate; And / or, the solvent is N,N-dimethylformamide.
33. The self-cleaning composite coating of claim 23, wherein: The amount of the initiator is 0.5-1.5% of the mass of the polymerization monomer; And / or, the initiator is purified by recrystallization.
34. The self-cleaning composite coating of claim 33, wherein: The amount of the initiator used is 1% of the mass of the polymerization monomer.
35. The self-cleaning composite coating of claim 23, wherein: When the polymerizable monomer is only the monomer A, the type of the crosslinking agent is N,N-methylenebisacrylamide, and the amount of the crosslinking agent is 0-5% of the molar amount of the polymerizable monomer, excluding 0%; When the polymerizable monomers are the monomer A and the monomer B, the molar ratio of the monomer A to the monomer B is 1:1 or more; The monomer B is the methyl acrylate, the methyl methacrylate, the styrene, the methoxyethyl acrylate or the n-butyl methacrylate.
36. The self-cleaning composite coating of claim 35, wherein: When the polymerizable monomers are the monomer A and the monomer B, the molar ratio of the monomer A to the monomer B is 1.5:1 or more; The monomer B is the methyl acrylate or the n-butyl methacrylate; When the polymerizable monomer is only the monomer A, the amount of the crosslinking agent is 0-1% of the molar amount of the polymerizable monomer, excluding 0%.
37. The self-cleaning composite coating of claim 36, wherein: When the polymerizable monomers are the monomer A and the monomer B, the molar ratio of the monomer A to the monomer B is 2:1, 4:1, 5:1, 8:1 or 10:
1.
38. The self-cleaning composite coating of claim 23, wherein: The polymerizable monomers are the 2-(perfluorooctyl)ethyl methacrylate and the methyl acrylate; When the polymerizable monomers are the 2-(perfluorooctyl)ethyl methacrylate and the methyl acrylate, the molar ratio of the 2-(perfluorooctyl)ethyl methacrylate to the methyl acrylate is (0.5-10):1; When the polymerizable monomers are the 2-(perfluorooctyl)ethyl methacrylate and the methyl acrylate, the raw materials further include a crosslinking agent; the type of the crosslinking agent is N,N-methylenebisacrylamide, and the amount of the crosslinking agent is 0-5% of the molar amount of the polymerizable monomers; and / or, the polymerizable monomers are the 2-(perfluorooctyl)ethyl methacrylate and the n-butyl methacrylate; When the polymerizable monomers are the 2-(perfluorooctyl)ethyl methacrylate and the n-butyl methacrylate, the molar ratio of the 2-(perfluorooctyl)ethyl methacrylate to the n-butyl methacrylate is (0.5-10):
1.
39. The self-cleaning composite coating of claim 38, wherein: When the polymerizable monomers are the 2-(perfluorooctyl)ethyl methacrylate and the methyl acrylate, the molar ratio of the 2-(perfluorooctyl)ethyl methacrylate to the methyl acrylate is (1-8):1; When the polymerizable monomers are the 2-(perfluorooctyl)ethyl methacrylate and the n-butyl methacrylate, the molar ratio of the 2-(perfluorooctyl)ethyl methacrylate to the n-butyl methacrylate is (1-8):1; When the polymerizable monomers are the 2-(perfluorooctyl)ethyl methacrylate and the methyl acrylate, the amount of the crosslinking agent is 0-1% of the molar amount of the polymerizable monomers.
40. The self-cleaning composite coating of claim 39, wherein: When the polymerizable monomers are the 2-(perfluorooctyl)ethyl methacrylate and the methyl acrylate, the molar ratio of the 2-(perfluorooctyl)ethyl methacrylate to the methyl acrylate is 2:1, 4:1 or 5:1; When the polymerizable monomers are the 2-(perfluorooctyl)ethyl methacrylate and the n-butyl methacrylate, the molar ratio of the 2-(perfluorooctyl)ethyl methacrylate to the n-butyl methacrylate is 2:1, 4:1 or 5:
1.
41. The self-cleaning composite coating of claim 23, wherein: The initiator is added into the mixed solution containing the polymerization monomer to carry out the solution polymerization.
42. The self-cleaning composite coating of claim 41, wherein: The mixed solution is obtained by heating and stirring.
43. The self-cleaning composite coating of claim 42, wherein: The heating and stirring temperature is 60-70° C.; the heating and stirring time is 0.2-1 h.
44. The self-cleaning composite coating of claim 43, wherein: The heating and stirring temperature is 65° C.; the heating and stirring time is 0.5 h.
45. The self-cleaning composite coating of claim 23, wherein: The temperature of the solution polymerization is 60-70°C; And / or, the solution polymerization time is 20 to 30 hours; and / or, the polymerizable monomer accounts for 5-45% of the total mass of the polymerizable monomer and the solvent; And / or, the reaction solution after the solution polymerization is post-treated.
46. The self-cleaning composite coating of claim 45, wherein: The temperature of the solution polymerization is 62-68°C; And / or, the solution polymerization time is 24 h; and / or, the polymerizable monomer accounts for 10-30% of the total mass of the polymerizable monomer and the solvent; And / or, the post-treatment operations include: cooling, washing, filtering, and drying the obtained filter cake.
47. The self-cleaning composite coating of claim 46, wherein: The temperature of the solution polymerization is 65°C; And / or, the polymerized monomer accounts for 16.7-20% of the total mass of the polymerized monomer and the solvent.
48. The self-cleaning composite coating of claim 23, wherein: The thickness of the self-cleaning coating is 0.005-0.1 mm.
49. The self-cleaning composite coating of claim 48, wherein: The thickness of the self-cleaning coating is 0.02-0.06 mm.
50. A method for preparing a self-cleaning composite coating as claimed in any one of claims 23 to 49, comprising: A photothermal layer is prepared on a substrate, and then a self-cleaning coating according to any one of claims 23 to 49 is prepared on the photothermal layer.
51. The method for preparing the self-cleaning composite coating according to claim 50, characterized in that: The photothermal layer is prepared by immersion deposition, spray coating, spin coating or blade coating.
52. The method for preparing the self-cleaning composite coating according to claim 51, characterized in that: When the photothermal layer is (cationic polyelectrolyte / substance with photothermal conversion effect) n In the case of a multilayer film, the multilayer film is prepared by alternate immersion deposition.
53. The method for preparing the self-cleaning composite coating according to claim 51 or 52, characterized in that: When the photothermal layer is (PDDA / Mxene) n When multilayer film, the (PDDA / Mxene) n The multilayer films were prepared by alternating immersion deposition.
54. The method for preparing the self-cleaning composite coating according to claim 53, characterized in that: The operation includes: soaking the substrate in a PDDA solution for the first time, taking it out and washing it with water, and then soaking it in a Mxene dispersion for the second time, taking it out and washing it with water, that is, depositing a cycle of PDDA / Mxene multilayer film; repeating the above process n times, and obtaining (PDDA / Mxene) n Multilayer film.
55. The method for preparing the self-cleaning composite coating according to claim 54, characterized in that: The concentration of the PDDA solution is 0.1-10 mg / mL; The solvent of the PDDA solution is water; The first soaking time is more than 1 minute; The concentration of the Mxene dispersion is 0.01-10 mg / mL; The solvent of the Mxene dispersion is water; The second soaking time is more than 1 minute; Deionized water is used for the washing.
56. The method for preparing the self-cleaning composite coating according to claim 55, characterized in that: The concentration of the PDDA solution is 1 mg / mL; The first soaking time is 10 minutes; The concentration of the Mxene dispersion is 0.1 mg / mL; The second soaking time is 10 minutes.
57. The method for preparing the self-cleaning composite coating according to claim 51 or 52, characterized in that: When the photothermal layer is (PDDA / AuNPs) n When the multilayer film is (PDDA / AuNPs) n The multilayer films were prepared by alternating immersion deposition.
58. The method for preparing the self-cleaning composite coating according to claim 57, characterized in that: The operation includes: soaking the substrate in a PDDA solution for the first time, taking it out and washing it with water, and then soaking it in a gold nanoparticle (AuNPs) dispersion for the second time, taking it out and washing it with water, that is, depositing a cycle of PDDA / AuNPs multilayer film; repeating the above process n times, (PDDA / AuNPs) is obtained. n Multilayer film.
59. The method for preparing the self-cleaning composite coating according to claim 58, characterized in that: in, The concentration of the PDDA solution is 0.1-10 mg / mL; The solvent of the PDDA solution is water; The first soaking time is more than 1 minute; The concentration of the AuNPs dispersion is 0.01-10 mg / mL; The solvent of the AuNPs dispersion is water; The second soaking time is more than 1 minute; Deionized water is used for the washing.
60. The method for preparing the self-cleaning composite coating according to claim 59, wherein: The concentration of the PDDA solution is 1 mg / mL; The first soaking time is 10 minutes; The concentration of the AuNPs dispersion is 0.1 mg / mL; The second soaking time is 10 minutes.
61. The method for preparing the self-cleaning composite coating according to claim 51 or 52, characterized in that: When the photothermal layer is a carbon nanotube layer, the carbon nanotube layer is prepared by spraying, and the operation includes: spraying a carbon nanotube dispersion on a substrate and drying.
62. The method for preparing the self-cleaning composite coating according to claim 61, characterized in that: in, The concentration of the carbon nanotube dispersion is 0.01-150 mg / mL; The solvent of the carbon nanotube dispersion is N-methylpyrrolidone, water or N,N-dimethylacetamide; The drying temperature is 20-200°C.
63. The method for preparing the self-cleaning composite coating according to claim 62, characterized in that: The concentration of the carbon nanotube dispersion is 10 mg / mL; The drying temperature is 70°C.
64. The method for preparing the self-cleaning composite coating according to claim 51 or 52, characterized in that: When the photothermal layer is a polydopamine layer, the polydopamine layer is prepared by immersion deposition, and the operation includes: immersing the substrate in a polydopamine solution, taking it out and drying it.
65. The method for preparing the self-cleaning composite coating according to claim 64, characterized in that: in, The concentration of the polydopamine solution is 0.1-100 mg / mL; The solvent of the polydopamine solution is water; The soaking time is 1 to 10 days; The drying is natural drying at room temperature.
66. The method for preparing the self-cleaning composite coating according to claim 65, characterized in that: The concentration of the polydopamine solution is 2 mg / mL; The soaking time is 3 days.
67. Use of the self-cleaning composite coating according to any one of claims 23 to 49 in deicing, defrosting or dewaxing.
Citation Information
Patent Citations
Self-cleaning nano protective liquid used for glass and preparation method
CN105111875A
Conformal coating and preparation method thereof
CN109897493A
Anti-icing organic resin coating composition
JP1986095077A
Coating composition
JP2016204533A